Species diversity of Aspergillus section Versicolores in clinical samples and antifungal susceptibility. Issue 11 (November 2016) - Siqueira, João Paulo Zen; Sutton, Deanna A.; García, Dania; Gené, Josepa; Thomson, Pamela; Wiederhold, Nathan; Guarro, Josep
Abstract: Aspergillus section Versicolores includes species of clinical relevance and many others that have been poorly studied but are occasionally found in clinical samples. The aim of this study was to investigate, using a multilocus phylogenetic approach, the spectrum of species of the section Versicolores and to determine their in vitro antifungal susceptibility. The study was based on a set of 77 clinical isolates from different USA medical centres, which had been previously identified as belonging to this section. The genetic markers used were internal transcribed spacer (ITS), β-tubulin ( BenA ), calmodulin ( CaM ), and RNA polymerase II second largest subunit ( RPB2 ), and the drugs tested, following the CLSI guidelines, were amphotericin B (AMB), itraconazole, posaconazole, voriconazole, anidulafungin, caspofungin, micafungin, terbinafine (TBF), and flucytosine (5FC). The most frequent species were Aspergillus sydowii (26 %), Aspergillus creber (22 %), and Aspergillus amoenus (18.2 %), followed by Aspergillus protuberus (13 %), Aspergillus jensenii (10.4 %), and Aspergillus tabacinus (5.2 %); while Aspergillus cvjetkovicii, Aspergillus fructus, Aspergillus puulaauensis, and Aspergillus versicolor were represented by only one isolate each (1.3 %). This is the first time that A. jensenii and A. puulaauensis have been reported from clinical samples. Considering the high number of isolates identified as belonging to this fungal group in this study, its clinical relevance should not be overlooked. Aspergillus versicolor, traditionally considered one of the most common species in this section in a clinical setting, was only rarely recovered in our study. The in vitro antifungal results showed that echinocandins and TBF were the most potent drugs, the azoles showed variable results, AMB was poorly active, and 5FC was the less active.